2007
DOI: 10.1007/s00701-007-1151-z
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of solitary osteochondroma of the dens of the C2 vertebra

Abstract: We report an extremely rare case of a 22-year-old man with an asymptomatic osteochondroma of the dens of C2 vertebra accidentally found during a brain CT scan examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…62 Because up to 43% of spinal osteochondromas arise at the atlantoaxial level and 17% at C-7, they tend to occur at junctional-transitional areas. 13,39,51,59,60,64 Tubbs et al reported on a rare case of recurrent osteochondroma after incomplete resection. 65 Our literature review indicated that all patients with multiple hereditary exostosis should undergo MRI of the spine because 27% will have spinal lesions.…”
Section: Primary Bone Tumors Affecting the Atlantoaxial Skeleton Of Cmentioning
confidence: 99%
“…62 Because up to 43% of spinal osteochondromas arise at the atlantoaxial level and 17% at C-7, they tend to occur at junctional-transitional areas. 13,39,51,59,60,64 Tubbs et al reported on a rare case of recurrent osteochondroma after incomplete resection. 65 Our literature review indicated that all patients with multiple hereditary exostosis should undergo MRI of the spine because 27% will have spinal lesions.…”
Section: Primary Bone Tumors Affecting the Atlantoaxial Skeleton Of Cmentioning
confidence: 99%
“…A disease of growing bone, affecting males more frequently than females (2.5:1), OCs typically present in younger patients during the 2nd to 3rd decades of life; however, it has also been described in the 8th decade 4 9 10. Our patient presented in his second decade which is the commonest age of presentation.…”
Section: Discussionmentioning
confidence: 68%
“…Due to a low rate of malignant transformation, asymptomatic SOC can be followed conservatively 10. When the tumour causes pain or neurological complications due to compression, or the diagnosis is indefinite, it should be excised at its base.…”
Section: Discussionmentioning
confidence: 99%
“…As emerging from the literature, spinal OCs are rarely seen in elderly patients as the case here described 3 9 15. The pathological mechanisms governing their development in this age group are still not settled.…”
Section: Discussionmentioning
confidence: 82%